Kinnarā kinnarī - Citra, 1952- (Cā pe Bimānʻ thutʻ praññʻ sūʹ lakʻ cvai cā cañʻ, 1993)
On kinnara and kinnari, male and female of a Buddhist mythical animal, as depicted in Burmese art and literature.